Pengaruh Kualitas Pelayanan, Kualitas Produk, dan Harga Terhadap Kepuasan Konsumen Produk Adidas - Maulidiyah, Nailin Nikmatul; Hakim, Ikhwanul; Tumini, Tumini; Elmas, Muhammad Syarif Hidayatullah; Junaidi, Junaidi (Ecobuss, 2025)
The aim of this research is to determine "The influence of service quality, product quality and price on consumer satisfaction with Adidas products among Panca Marga University students who use Shopee." The type of research used in this research is a type of quantitative research that produces discoveries that can be achieved (obtained) using statistical procedures or other methods with measurement quantification. The data collection method in this research used interviews, documentation and questionnaires which were distributed to 100 respondents. The analysis in this research uses SPSS. The results of this research show that service quality has an influence on consumer satisfaction, but it is not significant, product quality and price have a significant effect on consumer satisfaction.